Healthcare practitioners’ views of postnatal depression: a qualitative synthesis - Mohd Arifin, Siti Roshaidai; Cheyne, Helen; Maxwell, Margaret (2018)
The World Health Organisation recommended that healthcare practitioners should have appropriate skills to assess psychological distress in women attending for antenatal and postnatal healthcare. However, little is known about the perceptions of healthcare practitioners on postnatal depression and its management. The aims of this review were: (i) to understand healthcare practitioners’ experience of caring for postnatal depression in different countries and cultures and (ii) to identify any qualitative study that has been specifically carried out in Malaysia on healthcare practitioners’ perceptions of postnatal depression. A qualitative synthesis of studies reporting healthcare practitioners’ experience of managing postnatal depression was conducted. CINAHL, PubMed, MEDLINE, PsyINFO and ASSIA databases were searched using specific key words, and published peer-reviewed articles from 2006 to 2016 were scanned for inclusion criteria. 15 studies on healthcare practitioners’ experience of caring for women with postnatal depression were reviewed. These were conducted in eight different countries: America, Australia, United Kingdom, Brazil, Canada, Greek, Mexico, and Slovenia. No study conducted in Malaysia was found. This review suggests that the experience of caring for women with postnatal depression across different countries was not totally different. Two main limitations in the management of postnatal depression were reported by the healthcare practitioners: lack of resources on maternal mental health and absence of policy regarding management of postnatal depression. Understanding of how Malaysian healthcare practitioners perceive and understand postnatal depression and their roles in managing postnatal depression is beneficial to uncover details of the management of postnatal depression in the clinical practices in Malaysia.